Impoliteness and turn taking in selected Gbas Gbos interaction among Nigerians on X - Tayo Adebayo; David Esuola (Yayasan Mitra Persada Nusantara, 2026)
Impoliteness strategies, a concept that underscores how people’s self-worth is bruised in interactions, have been investigated at different levels in Nigerian scholarship, particularly on social media. Most of these studies have been premised on socio-political issues, whereby Nigerians have employed impoliteness strategies towards government authority. Few studies have explored impoliteness and turn-taking strategies among Nigerians on X. This gap necessitated the present study to examine the impoliteness strategies and turn-taking in gbas gbos interaction among Nigerian netizens on X. The study’s data was collected using a purposive data collection approach from X social media platform. The data was bound by Culpeper’s (1996) impoliteness framework and conversation analysis by Harvey Sacks et al. (1975). The study’s findings unwrapped that gbas gbos interactions are marked with gross impoliteness, using strategies such as bald-on-record, positive, negative, and mock or sarcasm impoliteness. Conversational analysis via turn-taking highlighted how the participants observed turn-taking rules during the interaction.